Critical Study of Al-Dakhil from the Path of Isra’iliyat - Siregar, Suci Romadani; Indriyanti, Nur Aulia; Sahputra, Hery (AHKAM, 2025)
This study critically examines the phenomenon of al-dakhil within the context of Isra’iliyat narratives that have permeated the traditions of tafsir (Qur’anic exegesis) and hadith. Al-dakhil refers to interpretations lacking valid foundations, including weak (da‘if), fabricated (mawdu‘) reports, erroneous ta’wīl (interpretation), and ideologies inconsistent with core Islamic teachings. These narratives often stem from external sources primarily Jewish and Christian traditions, and are integrated into Islamic discourse, sometimes without critical scrutiny. Employing a qualitative methodology with a hermeneutic approach, this research explores the impact of Isra’iliyat on the development of Qur’anic exegesis and the resulting scholarly debates. The findings reveal that while Isra’iliyat has occasionally been used to supplement understanding of certain Qur’anic verses, its authenticity is frequently questionable, both in terms of sanad (chain of transmission) and matan (content). The study underscores the necessity for mufassirs (exegetes) to exercise discernment when engaging with Isra’iliyat, ensuring that interpretations remain faithful to Islamic principles. By highlighting the risks of uncritical acceptance of external narratives, this research contributes to a deeper understanding of the importance of methodological rigor and doctrinal integrity in Islamic scholarship.